PERAN DAN DAMPAK TEKNOLOGI DALAM PEMBELAJARAN PAI - Fadli Ramadhanul Aflah; Idham Kholis; Rivaldiansolih Lubis; Khairunnas Rajab; Yuliana Intan Lestari (STAI Ihyaul Ulum Gresik, 2026)
The rapid development of digital technology has brought significant changes in the world of education, including in Islamic Religious Education (PAI) learning. This article aims to examine the role and impact of technology in PAI learning, as well as to identify effective strategies for its use in the digital era. This study uses a library research method by analyzing literature sources such as national journals, reference books, and relevant actual case studies. The results of the study show that technology has an important role in PAI learning, both as interactive media, alternative learning resources, and evaluation tools. The positive impacts include increasing student learning motivation, expanding access to Islamic knowledge, and encouraging teacher creativity. However, challenges such as potential distractions, inequality of access, and low teacher digital literacy are still obstacles. A case study at MAN 2 Pekanbaru shows that appropriate use of technology can strengthen PAI learning outcomes. The conclusion of this article is that technology has great potential in enriching PAI learning, but it needs the support of appropriate pedagogical strategies and policies so that Islamic values ​​are maintained in the process of digitalizing education.